The difference between (3x+6y)(3x+6y) and (4x+9y)(4x+9y) is 7x² +36xy+45y²
<h3>What is an Expression ?</h3>
An expression is a mathematical statement which has variables , constants and mathematical operators simultaneously.
The expression given in the question is
(3x+6y)(3x+6y) and (4x+9y)(4x+9y)
the difference when (3x+6y)(3x+6y) is subtracted from (4x+9y)(4x+9y)
(4x+9y)(4x+9y) - (3x+6y)(3x+6y)
16 x² + 36xy+36xy +81y²-9x²-18x -18x -36y²
7x² +36xy+45y²
Therefore in simplest term , The difference between (3x+6y)(3x+6y) and (4x+9y)(4x+9y) is 7x² +36xy+45y²
To know more about Expression
brainly.com/question/15245739
#SPJ1
Answer:
Step-by-step explanation:
you have a special triangle 30-60-90
the ration in this traingle is x, x
, 2x, where 2x is the hypothenuse
the hypothenuse is 12
x=12/2=6
the other leg is 6
=10.39
Answer:
x = 12
Step-by-step explanation:
Angles in a triangle add up to equal 180 degrees
Hence, 10x - 11 + 3x - 2 + 3x + 1 = 180
( note that we just created an equation that we can use to solve for x )
we now solve for x using the equation we created
10x - 11 + 3x - 2 + 3x + 1 = 180
step 1 combine like terms
10 + 3x + 3x = 16x
- 11 - 2 + 1 = -12
we now have 180 = 16x - 12
step 2 add 12 to each side
- 12 + 12 cancels out
180 + 12 = 192
we now have 192 = 16x
step 3 divide each side by 16
16x / 16 = x
192 / 16 = 12
we're left with x = 12
Answer:
7
Step-by-step explanation:
8x-2y=48, replace y with 4, 8x-2(4)=48, multiply, 8x-8=48, add 8 to both sides to remove the -8, 8x=56 and finally divide by 8 to remove 8 from x, x=7.
Answer:
14 liters
Step-by-step explanation:
10 liters : 4 liters of juice and 6 liters of water
4/10 of juice and 6/10 of water
make it to 70% of juice and 30% of water
add 14 liters of juice
14/20=70% of juice
6/20=30% of water